Spatial-temporal differentiation and influencing factors of ecosystem health in Three-River-Source national Park - Yanqin Wang; Huaju Xue; Aiqing Li; Xiaofan Ma; Ailing Sun; Jinhe Zhang (Ecological Indicators)
Ensuring and maintaining ecosystem health is the goal of ecological protection and environmental governance. Exploring the spatial–temporal differentiation and influencing factors of ecosystem health in national parks is a crucial foundation for promoting the construction of ecological civilization and the high-quality development of national parks. Taking Three-River-Source National Park (TNP) as a case study, this paper adopts multi-source data to quantitatively evaluate the spatial and temporal variations of ecosystem health within TNP from 2000 to 2020 by constructing the measurement model of “Vigor-Service-Resilience”. It reveals the independent and interactive effects of its influencing factors. We found that: (1) Despite the overall positive trend observed in TNP’s ecosystem health, the trend remains relatively weak, and the health level predominantly dominated by the fragile level during the study period. (2) The spatial variation in ecosystem health within TNP was pronounced, with a noticeable increase moving from the northwest to the southeast area. It also showed significant “high-high” and “low-low” clustering effects in the eastern and northwestern regions. (3) Among all the indicators assessed, ecosystem vigor was the indicator that contributed the most to the growth of the ecosystem health index. (4) Variations in ecosystem health of TNP were mainly shaped by land use intensity and precipitation, and interactions between natural environmental factors and human activity factors enhanced the explanation of these changes. This study emphasizes the importance of ecosystem health in national parks and provides practical management recommendations for sustainable ecosystem development in national parks.